Cytomegalovirus‐negative kidney transplant recipients are at an increased risk for malignancy after kidney transplantation. Issue 9 (6th July 2016) - Rozen‐Zvi, Benaya; Lichtenberg, Shelly; Green, Hefziba; Cohen, Ori; Chagnac, Avry; Mor, Eytan; Rahamimov, Ruth
Abstract: Background: The effect of cytomegalovirus (CMV) serology status on malignancy risk in kidney transplanted patients is not clear yet. Methods: In a nested case–control study, CMV serology status was compared between patients with a malignancy and 2:1 matched control patients without a malignancy. In a cohort study, the hazard of malignancy was compared between patients that were CMV‐negative but had a CMV‐positive donor and other patients, using Cox analysis. Results: Fifty‐two of 599 patients transplanted in our center between 2001 and 2014 developed a malignancy. Nine (17.3%) of the 52 patients that developed cancer were CMV‐negative but had a‐CMV‐positive donor compared with 6 (5.8%) of the 104 matched control patients (odd ratio 3.42, 95% confidence interval [CI] 1.15–10.2, P =.021). By univariate Cox model, there was a trend toward increased cancer risk in CMV‐negative patients with a positive donor (hazard ratio [HR] 1.95, 95% CI 0.95–4.0, P =.07), but after adjusting for multiple covariates, CMV‐negative status was significantly associated with increased risk of cancer (HR 2.55, 95% CI 1.23–5.26; P =.012). Conclusions: CMV‐negative patients that had a CMV‐positive donor were found to have a higher risk of malignancy after kidney transplantation.